Bibliometric Analysis of Research Trends in Organic foods: A Retrospective Scientometric Overview (2014-2023) - Abrar , K. Mohammed; Verma, Anil (Journal of Ecohumanism, 2024)
This study shows how the organic food manufacturing industry has grown and changed over the last ten years. It also gives useful information about important publications, countries, and top journals in the field. There aren’t many full bibliometric analyses of the organic food manufacturing business. This study fills that gap by looking at research trends, important publications, and country-specific contributions over the last ten years. To look at study contributions and trends in the business of making organic food. The study uses VOS Viewer and R Studio to do bibliometric analysis on 738 papers from the Scopus database (2014–2023). It looks at things like citations, co-authorship networks, bibliographic coupling, and journal impact. The study shows that organic food research grew a lot from 2014 to 2023. The countries that got the most mentions were Australia and Bangladesh. Based on publication influence and citation metrics, it also lists the ten most important journals and the most unique organic foods. Researchers, policymakers, and industry stakeholders can use the study to find key research trends, leading countries, and important journals. This helps them make better decisions in the organic food manufacturing sector.